Prolonged Serum Alanine Aminotransferase Elevation Associated with Isotretinoin Administration. (17th July 2019) - Nazarian, Roya S.; Zheng, Elizabeth; Halverstam, Caroline; Cohen, Steven R.; Wolkoff, Allan W.
Abstract : Isotretinoin is a highly effective oral retinoid derivative for severe forms of acne. Despite its high margin of safety, isotretinoin carries a risk of teratogenicity and mild to massive elevations of serum cholesterol and triglyceride levels, as well as infrequent transaminitis. Liver dysfunction induced by isotretinoin is rare but it poses a management dilemma. We describe a 16-year-old male in whom alanine aminotransferase (ALT) rose from a baseline of 13 to 288 U/L after 20 weeks of treatment with 1.0-1.4 mg/kg of oral isotretinoin daily. Though the patient remained asymptomatic, ALT levels did not return to normal limits for approximately 8 months after discontinuation of therapy, an observation that has not been documented in the literature. When oral isotretinoin was readministered for intractable facial acne 3 years later, liver enzymes remained normal throughout the course of therapy. Although the pathogenesis and prognosis of retinoid-induced hepatotoxicity are unknown, this case illustrates that isotretinoin may be safely readministered after normalization of liver function tests.